2011
DOI: 10.4028/www.scientific.net/amr.278.399
|View full text |Cite
|
Sign up to set email alerts
|

A1-L1<sub>2</sub> Structures in the Al-Co-Ni-Ti Quaternary Phase System

Abstract: The phase constituents of alloys from the (Ni,Co) 85 (Al,Ti) 15 plane of the Ni-Co-Al-Ti quaternary system were investigated following prolonged exposure at 750°C. Microstructural investigations confirmed the existence of a continuous A1-L1 2 two-phase region in the Ni-Co-Al-Ti quaternary system between Ni-Ni 3 Al and Co-Co 3 Ti. The lattice misfits of alloys from this quaternary system were determined using neutron diffraction. With increasing contents of Ti the positive lattice misfit increases up to +0.79% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Such modifications were shown to confer benefits to both the strength and microstructural stability of both cast & wrought [47][48][49][50][51] and powder processed [52,53] alloys. In parallel, fundamental studies of the underpinning Ni -CoAl -Ti system were performed and determined that the A1 -L1 2 two-phase field is continuous between Ni -Ni 3 Al and Co -Co 3 Ti [54,55]. More recently, Oni et al [56] employed a range of advanced characterisation techniques to study the site occupancies and lattice misfit strains in quaternary Ni-Co-Al-Ti alloys, and demonstrated a more complicated partitioning and site occupancy behaviour for Co than initially expected.…”
Section: Introductionmentioning
confidence: 99%
“…Such modifications were shown to confer benefits to both the strength and microstructural stability of both cast & wrought [47][48][49][50][51] and powder processed [52,53] alloys. In parallel, fundamental studies of the underpinning Ni -CoAl -Ti system were performed and determined that the A1 -L1 2 two-phase field is continuous between Ni -Ni 3 Al and Co -Co 3 Ti [54,55]. More recently, Oni et al [56] employed a range of advanced characterisation techniques to study the site occupancies and lattice misfit strains in quaternary Ni-Co-Al-Ti alloys, and demonstrated a more complicated partitioning and site occupancy behaviour for Co than initially expected.…”
Section: Introductionmentioning
confidence: 99%
“…[14] From the lattice constants of the phases, a g and a g 0 , the lattice misfit d was calculated then by the following formula: A specimen with a diameter of 5 mm was investigated in transmission geometry with a photon energy of 87 keV (l ¼ 0.1425 A ).…”
Section: Methodsmentioning
confidence: 99%
“…Kuhn et al pointed out that the matrix channels running perpendicular and parallel to the stress axis [001], respectively, contribute in different ways to the reflection profile due to the tetragonal distortion of γ due to coherency stresses [17]. Neutron diffraction measurements on homogeneous Ni-Co-Al-Ti alloys with high lattice misfit [18] and X-ray experiments by Royer et al [19] have confirmed that high coherency stresses in the matrix channels leads to a tetragonal distortion of the γ matrix. The fact that all alloys investigated in this study possess the same Re content and have been subjected to similar solution heat treatments suggests that a similar residual Re segregation may be expected between the alloys.…”
Section: Euro Superalloys 2010mentioning
confidence: 99%